Resettlement of British and Irish Catholics to Continental Europe in 16th—18th Centuries - V. Yu. Apryshchenko; N. А. Lagoshina (Научный диалог, 2021)
The problem of large-scale migration of British and Irish Catholics to continental Europe in the 16th—18th centuries is investigated. The relevance of the study is due to the fact that the religious schools of Catholics in Europe were seen as examples of pious communities, the foundations on which the emerging traditions of religious tolerance, stability and commercial prosperity were built in England. It is noted  that  this  fueled  the  arguments  of the supporters of liberal religious reforms in the UK in the 19th century. The novelty   of the study is seen in the fact that the study of the movement of Catholics to Europe makes  it  possible  to   reveal   the   degree   of influence of religious schools on British politics and public opinion, to understand how the expatriate community in exile functioned, adapted and communicated. Migration has been proven to be most intense during the Elizabethan period and early Stuart  reign,  but its impact on religious life in Britain and Ireland was felt over a longer period, until  the end of the 18th century. The authors conclude that for Catholics who remained in England, religious institutions in Europe were not only a source of supply of missionary priests and religious literature, but also a link with the continental Counter-Reformation.